Blended and Online Mode of Teaching and Learning: The Need of the Hour - Dr Tanuja Bhatt (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The year 2020 has been severely impacted by the COVID-19 epidemic, which has caused the whole globe to suffer a socioeconomic catastrophe and is harming humans on all fronts. The most severe setback is that the global education system is being severely impaired due to the implementation lockdown and the closure of schools and institutions. During this pandemic situation, blended and online learning played a vital role in imparting education to different students. This study explores the extra dimension and various significance of blended and online learning in this pandemic situation. The researcher followed the conceptual, qualitative research method for this study. In the end, the study concluded that blended e-learning is using various e-learning technologies in classroom instruction to improve the teaching and learning experiences of students and teachers by allowing them to engage more proactively.